Nurses' satisfaction with the use of communication channels by their managers in Croatia and Slovenia - Starc, Jasmina, ekonomistkinja (Array, 2019)
Previous studies rather neglected the issue of how nurses are satisfied with the usage of communication channels by their managers. This paper aims to discover how nurses in Croatia and Slovenia are satisfied with their managers’ usage of communication channels, and also how this satisfaction is associated with the employee-organisation relationship. A self-administrated electronic questionnaire was conducted with 272 nurses in Croatia and Slovenia. The study results show that top nurse managers most commonly use mediated communication channels, while middle and executive nurse managers use more interpersonal communication channels. Employees are most satisfied when top nurse managers use emails, middle nurse managers face-to-face communication, emails and phone calls, and executive nurse managers face-to-face communication, emails, phone calls, instant messaging and internal social networks to communicate with them. Younger employees are significantly more satisfied with nurse managers’ use of new communication and information technologies. The study also shows that satisfaction with interpersonal communication used by the executive nurse managers is positively associated with employee-organization relationships and satisfaction with middle and top managers’ utilization of email in that relationship.